Mango butter financial feasibility analysis: value added in the Chittoor District, Andhra Pradesh, India - Pendurthi, Sita Mahalakshmi (Kansas State University, 2018)
Mango butter is one of the byproducts from mangos that is mostly used in the cosmetic and soap industry. Hydraulic pressing is one way to extract the oil from the mango kernel. Hydraulic pressing is more cost effective for small scale processors due to both a relatively lower initial and operating cost. Moreover, the processing produces uncontaminated oil and a pure cake residue when compared to screw press or solvent extraction method. This thesis was undertaken to study the financial feasibility of value added to the mango by manufacturing mango butter in the Chittoor district, Andhra Pradesh India. The Totapuri mango variety is studied. A number of locations in India were evaluated for the manufacturing unit location considering the area of production, mango productivity and the presence of pulp factories for raw material sourcing. The analysis indicated that the Chittoor district in Andhra Pradesh, India has a cluster of mango pulp factories that are reliable sources of raw material. Indian consumers are generally quick to adopt new products with better experiences and more convenience. This study identifies additional uses for mango butter in countries that consume mango butter, and highlights products with which mango butter would be in competition. The advantages and limitations of competitors producing in the Indian market are discussed. The recommendation of this study is that entrepreneurs should study the sector thoroughly before investing in mango butter production. Project size and outlay of the depend upon the market size, the type of technology that will be used and how automated the project will be. New entrepreneurs may partner with existing merchant exporters initially to gain entry into international markets. Once entry is obtained, vast export potential for such products can be slowly tapped.
Keywords: Mango; Value added; Chottoor District; Andhra Pradesh; Production